Alejandra Laera, Ficciones del dinero. Argentina, 1890-2001, Buenos Aires, Fondo de Cultura Económica, 2014, 395 páginas. - Davobe, Juan Pablo (Universidad Nacional de Quilmes, 2015)
Fil: Dabove, Juan Pablo. University of Colorado Boulder; Estados Unidos.